To Merge or to License: Implications for Competition Policy - Ramon Fauli-Oller; Joel Sandonis (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2000)
The optimal merger policy when efficiency gains are not merger specific but can also be achieved through licensing is derived in a differentiated goods Cournot duopoly. We show that whenever both royalties and fees are feasible instruments to license technology, mergers should not be allowed, which fits the prescription of the U.S. Horizontal Merger Guidelines. When only one instrument is feasible, however, the possibility of licensing cannot be used as a definitive argument against mergers.
Keywords: 330